2009
DOI: 10.1063/1.3106086
|View full text |Cite
|
Sign up to set email alerts
|

Grazing exit versus grazing incidence geometry for x-ray absorption near edge structure analysis of arsenic traces

Abstract: In the presented study the grazing exit x-ray fluorescence was tested for its applicability to x-ray absorption near edge structure analysis of arsenic in droplet samples. The experimental results have been compared to the findings of former analyses of the same samples using a grazing incidence ͑GI͒ setup to compare the performance of both geometries. Furthermore, the investigations were accomplished to gain a better understanding of the so called self-absorption effect, which was observed and investigated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 27 publications
(26 reference statements)
1
21
0
Order By: Relevance
“…Based on these results, the same authors studied the applicability of the inverse TXRF geometry -the grazing exit (GE) set-up -to XANES analysis [50], because it was suggested that a normal incidence-grazing-exit geometry would not suffer from self-absorption effects in XAFS analysis due to the minimized path length of the incident beam through the sample. Their results proved this assumption and, in turn, confirmed the occurrence of the self-absorption effect for TXRF geometry.…”
Section: Sr-txrf-xafs Analysismentioning
confidence: 99%
“…Based on these results, the same authors studied the applicability of the inverse TXRF geometry -the grazing exit (GE) set-up -to XANES analysis [50], because it was suggested that a normal incidence-grazing-exit geometry would not suffer from self-absorption effects in XAFS analysis due to the minimized path length of the incident beam through the sample. Their results proved this assumption and, in turn, confirmed the occurrence of the self-absorption effect for TXRF geometry.…”
Section: Sr-txrf-xafs Analysismentioning
confidence: 99%
“…[18] At SR sources, GEXRF can be combined in addition with X-ray absorption spectroscopy that allows to study, for example, the local electronic structure of implanted dopants. [8,19] SR enhances, thus significantly, the versatility of possible GEXRF applications.…”
Section: Gexrf Methodologymentioning
confidence: 99%
“…Consequently, GIXRF offers about one order of magnitude better detection limits for trace impurities compared with GEXRF. [8] However, GIXRF setups are not versatile with respect to the type of the primary beam, and it is not possible to combine them with wavelength-dispersive detection setups to profit from the advantages related to the high energy resolution offered by the latter.…”
Section: Introductionmentioning
confidence: 99%
“…The performances of both grazing XRF techniques have previously been compared on a theoretical basis to evaluate the detection limits 21 and on an experimental basis by using a plate beamguide 22 or by studying arsenic traces on wafer surfaces. 23 The general conclusion from these studies is that, despite the better signal-to-background ratios offered by wavelength-dispersive GEXRF setups, GIXRF provides better detection limits because of the higher luminosity of grazing incidence setups. For Al surface contaminations on silicon, detection limits of 3.7 Â 10 12 cm À2 for GEXRF 24 and 2 Â 10 9 cm À2 for total-reflection XRF 25 (TXRF) were reported.…”
Section: Gixrf and Gexrfmentioning
confidence: 99%